2015
DOI: 10.1016/j.neuron.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Tracing Using Cux2-Cre and Cux2-CreERT2 Mice

Abstract: This Matters Arising paper is in response to Guo et al (2013) in Neuron. See also the Matters Arising by Eckler et al. published concurrently. Using genetic fate-mapping with Cux2-Cre and Cux2-CreERT2 mice we demonstrated that the neocortical ventricular zone (VZ) contains radial glial cells (RGCs) with restricted fate potentials (Franco et al., 2012). Using the same mouse lines, Guo et al. (2013) concluded that the neocortical VZ does not contain lineage restricted RGCs. We now show that the recombination pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 28 publications
4
67
0
Order By: Relevance
“…As the first ipsilateral axons are observed in the optic chiasm at around E16 (Colello & Guillery, 1990), we predict that our quantification at E15.5 (Figures 1 and 2) represents an accurate approximation of the number of Zic2 + RGCs in VT retina. However, our quantification of Zic2 + RGCs at E16.5 ( Figure 2) and, in particular, at E18.5 (Figure 3) (Franco et al, 2012;Gil-Sanz et al, 2015). In recent work, we have shown that a subset of i-and cRGCs that reside in VT retina originate from a spatially segregated progenitor pool localized to the CMZ .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As the first ipsilateral axons are observed in the optic chiasm at around E16 (Colello & Guillery, 1990), we predict that our quantification at E15.5 (Figures 1 and 2) represents an accurate approximation of the number of Zic2 + RGCs in VT retina. However, our quantification of Zic2 + RGCs at E16.5 ( Figure 2) and, in particular, at E18.5 (Figure 3) (Franco et al, 2012;Gil-Sanz et al, 2015). In recent work, we have shown that a subset of i-and cRGCs that reside in VT retina originate from a spatially segregated progenitor pool localized to the CMZ .…”
Section: Discussionmentioning
confidence: 75%
“…One question that remains unanswered is whether i‐ and cRGCs arise from a common progenitor pool or whether they originate from distinct fate‐restricted progenitor pools. Recent evidence in the developing cortex indicates that upper cortical neurons originate from a set of Cux2 + fate‐restricted progenitors, which challenges the classical view that all cortical neurons classes originate from a common multipotent progenitor pool that changes competence during time (Franco et al, ; Gil‐Sanz et al, ). In recent work, we have shown that a subset of i‐ and cRGCs that reside in VT retina originate from a spatially segregated progenitor pool localized to the CMZ (Marcucci et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…As Emx2 progenitors are also gliogenic, the almost complete absence of glial cells in the lineage of Cux2-expressing progenitors, a feature of a more restricted cell lineage, supports our view. However, as shown in recent articles, the Cux2-expressing traced lineages occupy a wider thickness of the cortical plate depending on the genetic background of the mouse strain (50,51). This fact makes it very difficult to establish the direct relationship between Emx2 progenitors that we observed in wild type and Cux2-expressing RGCs that were always described in transgenic mouse lines.…”
Section: Emx2 Progenitors Support Both the Restricted And The Sequentialmentioning
confidence: 73%
“…Recent studies have revealed that certain breeding strategies can influence Cre activity patterns (Gil-Sanz et al., 2015; Hayashi et al, 2003; Heffner et al, 2012; Kobayashi and Hensch, 2013; Rempe et al, 2006; Schmidt-supprian and Rajewsky, 2007). Since maternal versus paternal inheritance of the Cre gene has been shown to potentially affect Cre activity, we aimed to examine this issue in our Foxg1-IRES-Cre line.…”
Section: Resultsmentioning
confidence: 99%